Review: James Paul Gee, Social Linguistics and Literacies - Butorac, Donna (SAGE, 2013)
This is the fourth edition of Social Linguistics and Literacies, which speaks well for both its authority and the ongoing engagement of its author with the advancement of a sociocultural approach to discourse analysis. As a reviewer, I approach it in its own terms as a statement made in 2012.